Physics teaching, climate change issues, and generative artificial intelligence - Gumilar, Surya; Nopharipaldi, Slamet (Research in Physics Education, 2024)
Physics education has traditionally focused on conceptual understanding and real-world applications. However, integrating climate change issues into physics teaching is crucial for fostering environmental awareness. Climate change significantly impacts global sustainability, yet it remains inadequately addressed in formal education due to the absence of dedicated courses and interdisciplinary challenges. Many fundamental physics concepts, such as thermodynamics and measurement, are directly applicable to understanding climate change. By embedding climate-related discussions into physics instruction, educators can enhance students' scientific literacy and moral responsibility toward environmental issues. Meanwhile, the rapid development of Generative Artificial Intelligence (GenAI) presents new opportunities for education, including physics instruction. GenAI can serve as a personalized learning assistant, helping students engage with complex topics such as climate change while improving their critical thinking skills. Thus, leveraging GenAI to address climate change within physics education offers a promising pathway to enhance students’ learning experiences and environmental consciousness.